Paroxetine exposure skews litter sex ratios in mice suggesting a Trivers–Willard process. (27th February 2016) - Gaukler, Shannon Marie; Ruff, James Steven; Potts, Wayne K.
Lay Summary: Exposure to paroxetine, a commonly prescribed antidepressant, causes mice to produce more daughters than sons. Altering litter sex ratio can provide benefits to parents, and many hypotheses have been offered to explain this phenomenon. Here, we find that maternal exposure negatively influences sons more than daughters and that by biasing the sex ratio of their litters toward daughters, mothers increase their number of grandchildren. Abstract: While conducting a toxicity assessment of the antidepressant paroxetine (Paxil®), in wild-derived mice ( Mus musculus ), we observed that exposed dams (P0 ) produced female biased litters (32:68 M:F). Though numerous experimental manipulations have induced sex ratio bias in mice, none have assessed the fitness of the offspring from these litters relative to controls. Here, we retrospectively analyze experimentally derived fitness data gathered for the purpose of toxicological assessment in light of 2 leading hypothesis (Trivers–Willard hypothesis [TWH] and cost of reproduction hypothesis [CRH]), seeking to test if this facultative sex ratio adjustment fits into an adaptive framework. Control F1 males were heavier than F1 females, but no differences in mass were detected between exposed F1 males and females, suggesting that exposed dams did not save energy by producing fewer males, despite producing 29.2% lighter litters relative to controls. F1 offspring of both treatments were released into seminatural enclosures where fitness was quantified. In enclosures, the relative reproductive success of F1 -exposed males (compared with controls) was reduced by ~20% compared with the relative reproductive success of F1 -exposed females. Thus, exposed dams increased their fitness by adjusting litters toward females who were less negatively affected by the exposure than males. Collectively, these data provide less support that the observed sex ratio bias results in energetic savings (CRH), and more support for the TWH because fitness was increased by biasing litters toward female offspring. These mammalian data are unique in their ability to support the TWH through the use of relevant fitness data.